Novel Self-expanding Shape-Memory Bioresorbable Peripheral Stent Displays Efficient Delivery, Accelerated Resorption, and Low Luminal Loss in a Porcine Model. (February 2023) - Glushchenko, Leonid; Hubbard, Brad; Sedush, Nikita; Shchepochkin, Vladislav; Krupnin, Artur; Sharafeev, Aidar
Objective and Design: The search for improved stenting technologies to treat peripheral artery disease is trending toward biodegradable self-expanding shape-memory stents that, as of now, still suffer from the acute trade-off between deliverability and luminal stability: Higher deliverability leads to lower lumen stability, vessel recoil, and stent breakage. This study was aimed at the development and testing of a self-expanding bioresorbable poly(l, l -lactide-co-ε-caprolactone) stent that was designed to produce confident self-expansion after efficient crimping, as well as quick bioresorption, and sufficient radial force. Materials and Methods: Bench tests were employed to measure shape-memory properties, radial force, and hydrolytic degradation of the stent. The porcine model was employed to study deliverability, lumen stability, biocompatibility, and stent integrity. A total of 32 stents were implanted in the iliac arteries of 16 pigs with 15 to 180 day follow-up periods. The stented vessels were studied by angiography and histological evaluation. Results: Recovery of the diameter of the stent due to shape-memory effect was equal to 90.6% after 6Fr crimping and storage in refrigeration for 1 week. Radial force measured after storage was equal to 0.7 N/mm. Technical success of implantation in pigs (after the delivery implemented by pusher) was 94%. At 180 days, no implanted stents were found to be fragmented: All of the devices remained at the site of implantation with no stent migration and all stents retained their luminal support. Only moderate inflammation and neoepithelialization were detected by histological assessment at 60, 90, 120, and 180 days. Lumen loss at 180 days was less than 25% of the vessel diameter. Conclusions: The stent with the mechanical and chemical properties described in this study may present the optimal solution of the trade-off between deliverability and luminal stability that is necessary for designing the next generation stent for endovascular therapy of peripheral arterial disease.